Mergers and Acquisitions: Value Created or Value Destroyed - Arya, Bhavna (2009)
Mergers and Acquisitions have dominated today’s corporate world. It is a process through which business restructuring is undertaken. Mergers and acquisitions in India are on the rise. According to research, India has emerged as one of the top countries with respect to mergers and acquisition deals. The increased competition in the global markets has induced the Indian companies to go for mergers and acquisitions as an important strategic choice. The key factors responsible for mergers and acquisitions in India are favourable government policies, additional liquidity in the corporate sector and dynamic attitudes of Indian entrepreneurs. In this research, the reasons why companies desire to undertake mergers and acquisitions and the impact of such activities on the participating companies have also been discussed. Studies have suggested that mergers and acquisitions affect the senior executives, labour force and the shareholders. A lot of theories have proved that mergers and acquisitions improve the performance of the company through cost reduction, synergies, economies of scales and several other factors. The merger of Mittal and Arcelor has been discussed in the above context. A case study analysis is undertaken to see whether the two companies have benefited from the merger. An attempt is made to learn the outcome of the merger and evaluate the effect of merger on both the firm and the shareholder. Mergers and Acquisitions are considered to be an important tool in the growth strategy of the company. This dissertation aims to identify whether there has been any value creation by undertaking merger activity.